Pentoxifylline in Dogs With Osteoarthritis: Comparative Treatment and Efficacy Analysis With Meloxicam - Kurtuluş Parlak; Nuriza Zamirbekova Erdogan; Tugba Melike Parlak; Elgin Orçum Uzunlu; Burak Dik (Veterinary Medicine and Science, 2025)
ABSTRACT Background Osteoarthritis is a chronic joint disease that affects dogs and humans alike, with nonsteroidal anti‐inflammatory drugs (NSAIDs) being the primary drug treatment for pain relief. This study hypothesised that pentoxifylline could be a potent therapeutic option for canine osteoarthritis, offering superior benefits compared to meloxicam. The study aimed to mitigate inflammation and degeneration, safeguard joint integrity, and assess pentoxifylline's potential as a safer and more effective alternative to NSAIDs in osteoarthritis management. Methods 12 dogs with stifle osteoarthritis were divided into two groups: meloxicam (0.1 mg/kg, subcutaneous) and pentoxifylline (10 mg/kg, intramuscular). Clinical, radiological and biochemical examinations were conducted on days 0, 15, 30 and 60. Results The pain scores were significantly lower in the meloxicam group on days 30 and 60 (p < 0.05). However, both groups had similar scores for other clinical evaluations (p > 0.05). Serum C‐reactive protein (CRP) levels were lower in the pentoxifylline group on days 15 and 30, and serum IL‐1β levels were lower on days 15, 30 and 60 (p < 0.05). Moreover, cartilage oligomeric matrix protein (COMP) and bone alkaline phosphatase (bALP) levels in the pentoxifylline group showed a significant reduction on day 15 (p < 0.05). Pentoxifylline reduced osteocalcin in serum and hyaluronic acid concentrations in synovial fluid on days 15 and 30 (p < 0.05). However, the level of cross‐linked C‐telopeptide of type 2 collagen in urine significantly decreased following meloxicam treatment. Conclusion Meloxicam relieves pain by protecting joint cartilage, while even low doses of pentoxifylline enhance joint perfusion and combat inflammation. Future research should explore higher pentoxifylline doses and its potential synergy with NSAIDs for superior osteoarthritis management.